Darwin und Wallace als Entomologen. - Sachtleben, Hans (Contributions to Entomology = Beiträge zur Entomologie, 1959)
The author describes the studies of Darwin and Wallace in entomology and discusses their influence on the foundation of the theory of natural selection.